2013
DOI: 10.1086/674764
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative‐Stress Biomarkers in Patients with Pulmonary Hypertension

Abstract: This controlled, prospective, nonrandomized clinical investigation has as its chief strength the fact that it was done in humans with active disease and apparently on fairly modest therapeutic regimens. The aim was to present the results of oxidative-stress biomarkers in humans suffering from pulmonary artery hypertension (PAH). Inflammation and oxidative stress are essential in PAH with increased lipid peroxidation and reduced antioxidant defenses. Twenty-four adult patients of both sexes, with a mean age of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 19 publications
(39 reference statements)
2
43
0
Order By: Relevance
“…Although correlation does not mean causality, these findings corroborated the proposed role of ROS in the development of ILD [31]. Several studies have provided evidence of elevated oxidative stress and its biomarkers in patients with PAH [32,33]. On the other hand, ESR together with CRP were shown to be elevated in patients with dcSSc with elevated oxidative stress [12], CRP levels were in correlation with TAP serum levels in patients with SSc [15].…”
Section: Discussionsupporting
confidence: 57%
“…Although correlation does not mean causality, these findings corroborated the proposed role of ROS in the development of ILD [31]. Several studies have provided evidence of elevated oxidative stress and its biomarkers in patients with PAH [32,33]. On the other hand, ESR together with CRP were shown to be elevated in patients with dcSSc with elevated oxidative stress [12], CRP levels were in correlation with TAP serum levels in patients with SSc [15].…”
Section: Discussionsupporting
confidence: 57%
“…MDA can be detected by the thiobarbituric acid (TBA) using a colorimetric method based on MDA TBA reaction and form a pink color, so gauging MDA and all species reacting with this acid. 42 The MDA can be specifically measured by high performance liquid chromatography (HPLC). The same reaction occurs between MDA and TBA, but due to the apparatus of the fluorescence detector, only the MDA is identified, making this more specific test.…”
Section: Biomarkers Of Oxidative Stressmentioning
confidence: 99%
“…In recent years, extensive studies in both animal models and patients suggested that oxidative stress plays a key role in pathological remodeling of the pulmonary vasculature [4]. Excessive lipid peroxidation participates in the abnormal proliferation of PASMCs [5].…”
Section: Introductionmentioning
confidence: 99%